Effective constructive and composite heuristics for grouping printed circuit boards in the electronic assembly industry. Issue 10 (3rd October 2022) - Huang, Jiang-Ping; Pan, Quan-Ke; Suganthan, Ponnuthurai Nagaratnam
Abstract : This article addresses the printed circuit board (PCB) grouping problem (PGP) in the electronic assembly industry. First, a mathematical model of PGP is presented. Then, four heuristics based on an iterative scheme are proposed. Two of them are constructive heuristics and the other two are composite heuristics. Based on the problem-specific characteristics, a new solution representation that consists of PCB assignment and component assignment is proposed. For the constructive heuristics, one is based on a single PCB and the other is based on a pair of PCBs. The composite heuristics consist of the constructive heuristics and a local search method formed by three new operators. To test the effectiveness of the presented heuristics, 100 problem instances are designed according to the real-world production process. The experiments and comparisons show that the presented heuristics perform much better than those in the literature.